Biology : The unity and diversity of life - Shofner, Marcia; Sellers, Larry G.; Taylor, Jane B.; Jackson, John D.; Lewis, Larry; Pechenik, Jan A.; Smith, Denny (United States of America : Thomson/West, 2006)
We believe the material in this resource manual will help novice instructors establish good teaching practices as well as being useful to experienced professors. The information represents a consensus as to what might be most suitable.
CONTENTS 1 Invitation to biology 2 Lifes's chemical basis 3 Molecules of life 4 Cell structure and function 5 A closer look at cell membranes 6 Ground rules of metabolism 7 Where it starts - photosinthesis y otros 42 chapters more Appendix
Incluye Contents
Keywords: BIOLOGY; BIOLOGÍA